PROFIL SELF-ESTEEM SISWA KELAS VIII SMP NEGERI 36 BANDUNG - Inal Raynal; Afrilianto, Muhammad; Susanti, Desy (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research aims to analyze the profile of self-esteem among 8th-grade students at SMP Negeri 36 Bandung. Self-esteem is an essential aspect for students as it can influence how they present themselves in social and family environments, as well as impact both their academic and non-academic performance. The methodology employed in this research is quantitative descriptive involving 222 students as samples. Data were collected using a self-esteem questionnaire distributed to the students and analyzed using descriptive statistics. Based on the findings from the questionnaire results, it shows that the majority of students have self-esteem in the medium category, totaling 169 students or 78%, while the high category includes 27 students or 12%, and the low category includes 26 students or 12%. Furthermore, in the aspect of competence, there are 28 students in the high category, 169 in the medium category, and 25 in the low category. In the aspect of worthiness, there are 24 students in the high category, 169 in the medium category, and 29 in the low category. Specifically, students feel more competent in certain skills compared to feeling valuable overall. This study concludes that the development of positive self-esteem is very important for students' personal, social, academic, and career development.